A case study of learning organization practiced in halal food industry in Malaysia / Aini Ahmad and Norhaslinda Nordin - Ahmad, Aini; Nordin, Norhaslinda (Academy of Contemporary Islamic Studies (ACIS), 2017)
As the halal food industry grows, the discourse on the managerial issues in the industry becomes increasingly pivotal. Similar to other bodies, halal fraternities encounter managerial problem that is the insufficiency of quality management in the industry. In tandem with the popular concept of management expounded for respectful bodies named learning organization, this paper attempts to ascertain its application in two halal food companies. The discourse on the occurrence of learning organization in other entities is regular. Nevertheles, in halal food industry; the area stands remote from the hive of scrutiny. This study delve into two established halal manufacturers in an attempt to evaluate the occurrence of the purported characteristics based on the understanding of learning organization introduced by Ortenblad (2002). The meant understanding encompasses learning at workplace, the climate for learning, learning structure, and organizational learning. Through interview, this study ascertains the level of embracement for the characteristics intentionally and unintentionally achieved in both companies. The result shows that both halal food companies do practice some elements suggested in the purported learning organization. This study opines that learning organization can flourish in halal bodies with the condition that proper and serious initiatives are taken to implement it.